ANALISIS EFEKTIVITAS PENGELOLAAN PIUTANG PADA PERUSAHAAN UMUM DAERAH (PERUMDA) AIR MINUM TIRTA JENEBERANG KABUPATEN GOWA - Amir, Amir; Eka Puteri, Alfira; Amran, Amran; Muttalib, Abd (Universitas Patria Artha, 2025)
This study aims to analyze the effectiveness of accounts receivable management at the Regional Public Company of Tirta Jeneberang Water Supply (PDAM Tirta Jeneberang) in Gowa Regency. The research method used is qualitative by conducting in-depth interviews with the management of PDAM Tirta Jeneberang. The data collected includes accounts receivable management policies, billing procedures, and efforts made to reduce customer arrears. The results show that PDAM Tirta Jeneberang has a fairly good accounts receivable management policy and procedure, but there are still some obstacles in its implementation, such as the lack of customer awareness to pay bills on time and the limited human resources to conduct intensive billing. The efforts made by PDAM Tirta Jeneberang to address this problem include socializing to customers, providing discounts for timely payment, and improving coordination with local governments to assist in the billing process. Overall, the accounts receivable management at PDAM Tirta Jeneberang can be considered quite effective, but there is still a need for improvement and enhancement, especially in terms of increasing customer awareness and strengthening human resources to conduct more intensive billing.